Whole-beam self-focusing in fusion-relevant plasma. (7th December 2020) - Spiers, B. T.; Hill, M. P.; Brown, C.; Ceurvorst, L.; Ratan, N.; Savin, A. F.; Allan, P.; Floyd, E.; Fyrth, J.; Hobbs, L.; James, S.; Luis, J.; et al.
Abstract : Fast ignition inertial confinement fusion requires the production of a low-density channel in plasma with density scale-lengths of several hundred microns. The channel assists in the propagation of an ultra-intense laser pulse used to generate fast electrons which form a hot spot on the side of pre-compressed fusion fuel. We present a systematic characterization of an expanding laser-produced plasma using optical interferometry, benchmarked against three-dimensional hydrodynamic simulations. Magnetic fields associated with channel formation are probed using proton radiography, and compared to magnetic field structures generated in full-scale particle-in-cell simulations. We present observations of long-lived, straight channels produced by the Habara–Kodama–Tanaka whole-beam self-focusing mechanism, overcoming a critical barrier on the path to realizing fast ignition. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.